THE REGULATION OF EXECUTIVE REMUNERATION IN SOUTH AFRICA - Vela Madlela; Palollo Michael Lehloenya (Obiter, 2016)
Executive remuneration is one of the essential aspects of corporate governance that has attracted increasing attention in corporate circles and beyond in recent years. This comes in the wake of the global financial crisis of 2008 and the executive remuneration packages that are spiraling out of control. The increasingly excessive payments companies and financial institutions make to their management teams have given rise to growing consensus that executive remuneration needs to be controlled and regulated. Included among the identified causes of the problem are inter alia lack of transparency and accountability in determining executive remuneration, conflict of interests among those who determine executive remuneration, misalignment of management and shareholder interests, as well as inadequate protection of shareholder governance rights. The primary object of this paper is to examine the adequacy of the current regulatory framework in South Africa in addressing the challenges relating to executive remuneration. It further takes cognisance of the need for companies to achieve an appropriate balance between adequate regulation and the necessary flexibility in responding to the needs of different companies. The paper also makes proposals for reforming the current regulatory framework in a way that promotes fairness, transparency and accountability in executive remuneration.